Mega-fortresses in the South Caucasus: new data from Southern Georgia - Erb-Satullo, Nathaniel L.; Jachvliani, Dimitri; Higham, Richard; O’Neil Weber-Boer, Kathryn; Symons, Alex; Portes, Ruth (Cambridge University Press (CUP), 2025)
Contemporary global research on large settlements (both urban and non-urban) has prompted a reassessment of factors driving population aggregation. The rise of large fortress settlements in the South Caucasus c. 1500-500 BCE has the potential to contribute to this discussion. A comprehensive aerial and ground-based survey of the large fortress-settlement of Dmanisis Gora reveals its distinctive character. Substantial defensive walls and stone architecture in the outer settlement contrast with evidence for apparent low intensity of occupation. These results have implications for pastoralist-driven population aggregation in Eurasia and beyond.
Keywords: Archaeology; 4301 Archaeology; Middle East; Late Bronze Age; Early Iron Age; photogrammetry; aerial survey; settlement; pastoralism